Do We Appropriately Detect and Understand Singlet Oxygen Possibly Generated in Advanced Oxidation Processes by Electron Paramagnetic Resonance Spectroscopy? - Zong, Yang; Long Chen; Zeng, Yunqiao; Jun Xu; Hua Zhang; Xiaomeng Zhang; Liu, Wen; Wu, Deli (Environmental Science & Technology, 2023)
Electron paramagnetic resonance (EPR) spectroscopy using sterically hindered amine is extensively applied to detect singlet oxygen (1O2) possibly generated in advanced oxidation processes. However, EPR-detectable 1O2 signals were observed in not only the 1O2-dominated hydrogen peroxide (H2O2)/hypochlorite (NaClO) reaction but surprisingly also the 1O2-absent Fe(II)/H2O2, UV/H2O2, and ferrate [Fe(VI)] process with even stronger intensities. By taking advantage of the characteristic reaction between 1O2 and 9,10-diphenyl-anthracene and near-infrared phosphorescent emission of 1O2, 1O2 was excluded in the Fe(II)/H2O2, UV/H2O2, and Fe(VI) process. The false detection of 1O2 was ascribed to the direct oxidation of hindered amine to piperidyl radical by reactive species [e.g., •OH and Fe(VI)/Fe(V)/Fe(IV)] via hydrogen transfer, followed by molecular oxygen addition (forming a piperidylperoxyl radical) and back reaction with piperidyl radical to generate a nitroxide radical, as evidenced by the successful identification of a piperidyl radical intermediate at 100 K and theoretical calculations. Moreover, compared to the highly oxidative species (e.g., •OH and high-valence Fe), the much lower reactivity of 1O2 and the profound nonradiative relaxation of 1O2 in H2O resulted it too selective and inefficient in organic contaminant destruction. This study demonstrated that EPR-based 1O2 detection could be remarkably misled by common oxidative species and thereby jeopardize the understandings on 1O2.